Incremental Sheet Forming (ISF) - Kumar Y.; Kumar S. (My University, 2025)
Incremental sheet forming (ISF) process is an advanced flexible manufacturing process to produce complex 3D products. In conventional forming process, the products are produced by dedicated tools, i.e. die and punch. However, ISF does not require any dedicated tool. A laboratory setup of single-point incremental forming machine has been developed using a motion card to control the 3 servo motors for controlling individual 3-axis and spindle movement at IIT (BHU), Varanasi. The strain distribution on the sheet over the length of deformation has been computed. The surface quality of the products is found to be good. Simple simulation has also been carried out. © 2015, Springer India.